Web Applications with Javascript or Java: Volume 1: Constraint Validation, Enumerations, Special Datatypes - Wagner, Gerd; Diaconescu, Mircea (De Gruyter Textbook, 2017)
Today, web applications are the most important type of software applications.This textbook shows how to design and implement them, using a model-based engineering approach that covers general information management concepts and techniques and the two most relevant technology platforms: JavaScript and Java.